DEFINING DECEPTION - Masip, Jaume; Garrido, Eugenio; Herrero, Carmen (Anales de Psicología / Annals of Psychology, 2004)
In view of the relative disagreement among those studying deception as to how deception, the lie, or deceptive communication should be defined, an attempt is made to integrate the views of the most influential scholars in the field in order to formulate a comprehensive and clear-cut definition of deception. The starting point is Coleman and Kay’s (1981) elements of the prototypical lie, as well as Gerald Miller’s (1983; Miller & Stiff, 1993) notion of “deceptive communication.” Deception is defined as the deliberate attempt, whether successful or not, to conceal, fabricate, and/or manipulate in any other way, factual and/or emotional information, by verbal and/or nonverbal means, in order to create or maintain in another or others a belief that the communicator himself or herself considers false. Each term of this definition is discussed in detail and, in doing so, it becomes apparent that several deception theories and a variety of social psychology and communication contributions have been integrated to build it. In addition, some specific implications of the definition, such as the importance that the intentional element (the deliberate attempt) has for the legal system, are discussed. The aim of this paper is to contribute to reaching an agreement among social scientists on what should be understood as deception.